2023
DOI: 10.3847/2041-8213/acc93f
|View full text |Cite
|
Sign up to set email alerts
|

Pointlike Sources among z > 11 Galaxy Candidates: Contaminants due to Supernovae at High Redshifts?

Abstract: The recent searches for z > 11 galaxies using the James Webb Space Telescope have resulted in an unexpectedly high number of candidate objects, which imply at least 1 order of magnitude higher number density of z > 11 galaxies than the previously favored predictions. A question has risen whether there are some new types of contaminants among these candidates. The candidate sample of Yan et al., totaling 87 dropouts, is the largest one, and we notice that a number of these candidates are pointlike. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These diverse transients as different types of supernovae (SNe) can be direct probes to trace the cosmic star formation history in the early Universe and expand our understanding substantially about the physics of the events at the epoch of the cosmic dawn. Recent observations have demonstrated that very faint transients (mag ∼ 29) are abundant in the near-infrared images taken by JWST (Chen et al 2022b(Chen et al , 2022a(Chen et al , 2023Hu et al 2022c;DeCoursey et al 2023;Yan et al 2023cYan et al , 2023bYan et al , 2023a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These diverse transients as different types of supernovae (SNe) can be direct probes to trace the cosmic star formation history in the early Universe and expand our understanding substantially about the physics of the events at the epoch of the cosmic dawn. Recent observations have demonstrated that very faint transients (mag ∼ 29) are abundant in the near-infrared images taken by JWST (Chen et al 2022b(Chen et al , 2022a(Chen et al , 2023Hu et al 2022c;DeCoursey et al 2023;Yan et al 2023cYan et al , 2023bYan et al , 2023a.…”
Section: Introductionmentioning
confidence: 99%
“…Calculating the difference images accurately is also important in high-precision differential photometry, which is employed in the detections of microlensing events (Mao & Paczynski 1991;Sumi et al 2003Sumi et al , 2006Sumi et al , 2013 and exoplanet transits (e.g., Oelkers & Stassun 2018;Montalto et al 2020). Recent works also reveal that the highly structured JWST/NIRCam PSF exhibits prominent spatial variation across the field of view of up to 20% and shows significant temporal variations at a level of ∼3%-4% (Nardiello et al 2022;Yan et al 2023c;.…”
Section: Introductionmentioning
confidence: 99%